Development and experimental testing of an integrated prototype based on Stirling, ORC and a latent thermal energy storage system for waste heat recovery in naval application. (1st April 2022) - Catapano, F.; Frazzica, A.; Freni, A.; Manzan, M.; Micheli, D.; Palomba, V.; Sementa, P.; Vaglieco, B.M.
Highlights: Optimization of an integrated waste-heat recovery systems for naval uses. Integration of Stirling, ORC systems and a thermal storage system during a cruise. WHR control strategy satisfied the entire hot water demand through the heat storage. ORC and Stirling converted into electricity more than 10% of total energy recovered. Abstract: This paper focuses on an advanced energy system, able to increase the overall efficiency of ships by recovering the heat wasted by the propulsion system. A small-scale prototype has been realized, developed, and tested under realistic operating conditions of boat during a winter and summer cruise. The main novelty of the research that has been presented in this paper lies in a significant contribution by developing an integrated dynamic device for electrical production and thermal energy storage. It is based on a 1000 cm 3 light duty compression ignition engine coupled with a properly adapted Stirling Engine (SE), an Organic Rankine Cycle group (ORC) and a latent Thermal Energy Storage system (TES). All the components have been managed by means of a specifically developed electronic control, simulating two standard cruise profiles. Scaled engine power data have been imposed to simulate port, manoeuvring and open sea navigation phases. The consumption of hot water has been obtained by considering the typical hourly use profile of a cruise ship. It has been demonstrated that the proposed integrated system allows recovering all the thermal energy needed to satisfy the hot water request during the cruise, avoiding the use of auxiliary boilers. The results indicate a favourable effect because the recovered thermal energy represents the 7.7 % of the total energy consumed by fuel. The net electrical energy generated by ORC and Stirling engine resulted to be about 1 % of the total fuel energy consumption, respectively 0.8 % and 0.2 %. The developed prototype can be a useful tool in viability analysis and can easily be reproduced for several uses. In conclusion, the integration of different systems with an optimal integration and sizing of the thermal energy storage considerably improve the thermodynamic, economic and environmental results for future clean ships.